User perceptions of a point-of-use water filtration device: Qualitative, focus group study - Martha Grant Fuller; Josephine N. Najjuma; Frank G. Jacobitz; Keith Macdonald; Gad Ruzaaza Ndaruhutse (PLoS ONE, 2026)
Universal access to clean water is sixth of the United Nations sustainable development goals. It has not yet been achieved. Boiling water, for water purification, is cost prohibitive and polluting. Diarrheal diseases linked to unsafe water cause morbidity and mortality in young children in Uganda, where most if the rural population lacks access to treated water. Bacterial water contaminants include Escherichia coli and Salmonella Typhi . Community perceptions of water quality and mitigation efforts in rural Uganda is unknown. In the absence of safe drinking water, a low-cost method of water purification is needed. In vitro studies of plant xylem filtration found this technique successful in removing coliform bacteria and other pollutants. The purpose of this study was to explore perceptions of water quality impact on the lives and health of residents in a rural community in Southwestern Uganda and obtain reactions to a prototype point-of-use water filtration device to determine the possibility of implementing its use in this community. Qualitative descriptive analysis of translated transcripts of purposefully designed focus groups was conducted. Participants included 36 adult residents of a rural community in Uganda. Groups led by experienced Ugandan facilitators in the local language, no researchers from the USA were present. No participants had access to treated water, past efforts to improve water failed due to lack of follow-up. Community members were aware of the poor quality of their water and described water associated illnesses in family members. Obtaining and boiling water required time, money, and resources with households using an average of 142 liters of water/day. Response to the device was mixed, with some excited at the possibility of using it and others expressing concerns regarding durability and cost. Future efforts must address concerns about costs and durability of any point-of-use device and will require extensive planning for sustainability.